Female Entrepreneurs in Bandung City's Ciroyom Market: Financial Capability and Savings Attitudes - Ratih Kusumastuti (Cita konsultindo, 2023)
By using lifestyle as a moderating variable, the researcher is attempting to determine whether financial literacy can affect saving behavior in Pasar Ciroyom, Bandung City. The researcher employed the quantitative approach. The primary type of data was used. 117 female business actors who operated a booth at Bandung's Pasar Ciroyom made up the study's sample. Utilizing 54 respondents in various samples from the target population. A straightforward random sampling technique was used to collect data through the distribution of online and offline questionnaires. The WarpPls 7.0 program was combined with path analysis. According to the test results, lifestyle variables have a positive impact on financial literacy variables, and vice versa. Financial literacy variables also have a positive impact on saving behavior, and lifestyle has the power to mediate this relationship